Serial–parallel cooperative assembly approach for precision micro-assembly of axial holes - L. Dong; J. Ma; J. Ma; J. Cao; D. Wang (Mechanical Sciences)
The assembly of high-density axial holes represents a crucial step in integrating highly sophisticated components for electronic equipment. This process faces two primary challenges: stringent precision requirements and the need for robust control during delicate adjustments. Given the miniaturization of components, manual assembly becomes inefficient. To address these challenges, this study introduces a novel dual-robot assembly system. The system incorporates a serial robot for force-controlled compliant assembly of precision axial holes, leveraging joint force sensors for direct force-feedback control to ensure enhanced positional accuracy. Additionally, a parallel robot facilitates precise positional adjustments, with its positioning accuracy further refined through kinematic calibration techniques validated through rigorous simulations. Ultimately, the established dual-robot assembly experimental platform successfully demonstrated the precision assembly of high-density axial holes, offering robust technical support for the precise integration of highly integrated components in electronic equipment.